Pain, mindfulness, and placebo: a systematic review - Lopes, Alexandra; Sampaio, Rute; Tavares, Isaura (Frontiers in Integrative Neuroscience, 2024)
Pain is a complex phenomenon that is influenced by psychosocial variables, which include the placebo effect. The effectiveness of mindfulness-based interventions (MBIs) for pain have been demonstrated in experimental studies and systematic reviews, but the mechanisms of action are just starting to be established. It remains to be systematically evaluated whether the expectations of individuals experiencing pain can be manipulated during MBIs and what role placebo effects might play. To evaluate the 2 literature analyzing placebo effects in MBIs for pain, we performed a systematic review based on a search conducted at the databases Pubmed, Web of Science and SCOPUS. Our search revealed a total of 272 papers, of which only 19 studies were included (10 acute pain, 9 chronic pain), considering the inclusion and exclusion criteria, namely expectations and placebo effects. From the 19 included studies, 6 measured placebo effects only related to a pharmacological intervention used in the study and not to an MBI. The results of the few studies that were devoted to placebo effects of the MBIs indicate that placebo and expectations play a role in the MBIs effects in pain. Although expectations and placebo effects are frequently discussed in the context of mindfulness and pain research, these results show that these factors are still not routinely considered in experimental designs. However, the results of the few studies included in this systematic review highlight a clear role for placebo and expectancy effects in the overall effects of MBIs for acute and chronic pain that warrant routine measurement and further consideration in future studies. Additional research in this fascinating and challenging field is necessary to fully understand the connection of MBI and placebo/expectations and their effects in pain relief.